A Catalyst-Free Process for the Direct Oxidative Synthesis of Formanilides from Arylamines and Aldehydes under Air Atmosphere - Qin, Yuancheng; Cheng, Yuanyuan; Luo, Xubiao; Li, Mingjun; Xie, Yu; Gao, Yunhua (Synlett, 2015)
An efficient and catalyst-free process for the direct oxidative synthesis of formanilides from primary aromatic amines and aliphatic aldehydes has been developed under mild aerobic oxidation conditions. The isotope-labeling experiments indicated that the oxygen atom of the formanilide originated from dioxygen.
Keywords: catalyst-free; oxidative; formanilides; arylamines; aldehydes